Techno-economic analysis and environmental assessment of isobutene, sustainable aviation fuel, omega-3 and omega-6 oils, and sophorolipid production in integrated sugarcane biorefineries - Adua, Bright (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.